2015
DOI: 10.2514/1.j053837
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Jet-Noise-Shielding Methodology

Abstract: Ongoing research toward the reduction of environmental noise from aircraft is investigating the possible shielding of engine-noise sources by novel airframe configurations. To assess the noise-reduction benefits attainable from such configurations, it is necessary to develop appropriate acoustic evaluation tools. In this paper, a jet-noise-shielding-prediction methodology is described. The Tam-Auriault ("Jet Mixing Noise from Fine-Scale Turbulence," AIAA Journal, Vol. 37, No. 2, 1999, pp. 145-153) jet-noise mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Flight-test results from this research aircraft campaign demonstrated noise levels of 90 EPNdB as measured at a sideline of 500 ft, which for the time was considerably lower than comparable jet transport aircraft [72]. These aircraft efforts have also been aided by the classic and recent efforts toward predicting and modeling noise shielding effects of propulsive-airframe integration [76][77][78][79][80][81][82].…”
Section: Distributed Electric Propulsion Enabled Noise Reductionmentioning
confidence: 86%
“…Flight-test results from this research aircraft campaign demonstrated noise levels of 90 EPNdB as measured at a sideline of 500 ft, which for the time was considerably lower than comparable jet transport aircraft [72]. These aircraft efforts have also been aided by the classic and recent efforts toward predicting and modeling noise shielding effects of propulsive-airframe integration [76][77][78][79][80][81][82].…”
Section: Distributed Electric Propulsion Enabled Noise Reductionmentioning
confidence: 86%